Equilibrium and transfer in porous media 3 : applications, isothermal transport and coupled transfers - Daïan, Jean-François (Civil engineering and geomechanics series., 2014)
"This book provides a detailed analysis of the aspects required for the understanding of many experimental techniques in the field of porous media transport phenomena. It is aimed at students or engineers who may not be looking specifically to become theoreticians in porous media, but wish to integrate knowledge of porous media with their previous scientific culture, or who may have encountered them when dealing with a technological problem."--Provided by publisher